2009
DOI: 10.1016/j.jksus.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A preprandial and postprandial plasma levels of ghrelin hormone in lean, overweight and obese Saudi females

Abstract: Ghrelin is a novel gastrointestinal peptide hormone isolated from human and rat stomach. Ghrelin administration stimulates growth hormone secretion but also causes weight gain by increasing food intake and reducing fat utilization in rodents. This study aims to determine the plasma level of ghrelin under basal condition and in response to a standard meal and to elucidate the relationship between this peptide and anthropometric measures. Body mass index (BMI), anthropometric measurements were calculated and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…This is consistent with other study that revealed BMI was an independent determinant of plasma ghrelin levels (Zou et al, 2008). Other studies have also shown that overweight people have a higher postprandial ghrelin concentration than people with normal weight (Daghestani, 2009;Lomenick et al, 2008). However, those studies may not be compared directly, due to the variations in participants' characteristics such as age and gender.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other study that revealed BMI was an independent determinant of plasma ghrelin levels (Zou et al, 2008). Other studies have also shown that overweight people have a higher postprandial ghrelin concentration than people with normal weight (Daghestani, 2009;Lomenick et al, 2008). However, those studies may not be compared directly, due to the variations in participants' characteristics such as age and gender.…”
Section: Discussionsupporting
confidence: 90%
“…Preclinically, physiological ghrelin signalling has been shown to enhance post-prandial GLP-1 release[164], clinical obesity has however been associated with reductions in fasting ghrelin levels that may contribute to the reduced post-prandial GLP-1 release observed[168-170]. Conversely, clinical data exists to suggest that suppression of late post-prandial rises in ghrelin is one mechanism by which GLP-1 exerts its anorexigenic effect[126]; reduced post-prandial GLP-1 secretion in obesity potentially explaining the attenuated decreases of post-prandial serum ghrelin observed in this cohort[168-170,184,185] (Figure 9). …”
Section: A Role For Glp-1 In the Pathophysiology Of Clinical Obesitymentioning
confidence: 99%
“…Comparable results were elucidated by Barazzoni et al [35]in obese and lean Caucasians and Beasley et al [36]who found that overweight/obese individuals had lower ghrelin concentrations compared to normal weight individuals.In support of the same results, Daghestani [37] found that ghrelin concentrations decreased in overweight/obese Saudi females compared to lean ones; i.e. ghrelin levels were negatively associated with BMI.Castaneda et al [38] suggested that ghrelin itself is not the key cause of obesity and stated whether potentially low levels of ghrelin in obesity represent an adaptation to the positive energy balance or an increased sensitivity to ghrelin remains an open question.Zou et al [39]speculated that the lower ghrelin levels in obesity were part of negative feedback to inhibit appetite and body weight, but not the primary cause of obesity.Ghrelin plays an important role in the regulation of food intake.…”
Section: Discussionmentioning
confidence: 79%